Sex and heredity are determinants of drug intake in a novel model of rat oral oxycodone self‐administration. (16th September 2021) - Sharp, Burt M.; Fan, Xinyu; Redei, Eva E.; Mulligan, Megan K.; Chen, Hao
Abstract: The steady rise in prescription opioids such as oxycodone has led to a virulent epidemic of widespread abuse and deaths in the United States; approximately 80% of affected individuals initiate the habitual use of oxycodone by using prescription oral oxycodone. Given the importance of drug pharmacokinetics in determining abuse potential, we designed an oral operant oxycodone self‐administration (SA) procedure in rats to model drug intake by most human users/abusers of oxycodone. Key aspects of the model include limited initial drug intake followed by increasing drug concentrations during extended 4‐h sessions on alternating days. Sex and genetic predisposition are major determinants of human opiate abuse. Therefore, we studied females in seven inbred strains (WLI, WMI, LEW, DSS, F344, BN and SHR) and both sexes in three of these strains. All strains increased intake across serially increasing doses (0.025–0.2 mg/ml; p  < 0.001): the range of intakes at the final concentration of oxycodone was 0.72 ± 0.17–4.84 ± 1.42 mg/kg (mean ± SEM) ‐ a 6.7‐fold difference across strains. In LEW, WLI and WMI strains, oxycodone intake increased significantly across all sessions in both sexes. However, in LEW and WMI male rats but not WLI, daily oxycodone intake was significantly lower across all 4‐h sessions than females ( p  < 0.005). The estimated heritability in oxycodone intake was in the range of 0.21–0.41. In summary, our novel operant oral oxycodone SA model captures the strong abuse potential of oral oxycodone and shows dose, sex and strain‐specific drug intake that is significantly dependent on heredity. Abstract : Seven inbred strains of rats show different dose‐dependent escalation of operant responses for oral oxycodone.